A 12 year experience of colistin resistance in Klebsiella pneumoniae causing neonatal sepsis: two-component systems, efflux pumps, lipopolysaccharide modification and comparative phylogenomics. (22nd March 2022) - Naha, Sharmi; Sands, Kirsty; Mukherjee, Suchandra; Dutta, Shanta; Basu, Sulagna
Abstract: Background: Increased use of colistin in healthcare necessitates studies on the trend of colistin resistance and the underlying mechanisms. Objectives: To understand the susceptibility trend and molecular mechanisms of colistin resistance in neonatal isolates over a 12 year period. Methods: Colistin susceptibility, mRNA expression, whole genome sequence and mutational analysis was performed. Phylogenomic comparison with a global collection of colistin-resistant Klebsiella pneumoniae strains ( n  = 70) was done. Results: Of 319 Enterobacterales ( K. pneumoniae and Escherichia coli ) studied, colistin resistance was found in 9 K. pneumoniae (2.8%). The transmissible colistin resistance gene, mcr, was absent. Colistin-resistant K. pneumoniae belonged to diverse sequence types (ST14/37/101/147/716) and exhibited multiple mechanisms of colistin resistance including overexpression of the two-component systems (TCS) ( phoP/Q, pmrA/B ), and AcrAB-TolC pump and its regulators. Mutations in TCS, mgrB, pumps, repressors, and lipopolysaccharide-modifying genes were detected. Phylogenomic comparison revealed that this global collection of colistin-resistant K. pneumoniae was diverse, with the presence of epidemic and international clones. Mutations in mgrB and TCS noted in global strains were comparable to the study strains. Co-occurrence of carbapenem resistance ( n  = 61, 87%) was observed in global strains. Co-existence of dual carbapenemases ( bla NDM-5 with bla OXA-48/181 ) in multiple lineages within different replicons was found in neonatal colistin-resistant study isolates only. Conclusions: Colistin resistance both in study and global strains is multifaceted and attributed to mutations in chromosomal genes leading to lipopolysaccharide modification or efflux of colistin through pumps. With no transmissible mcr, prevalence of colistin-resistant strains was low in this unit. Colistin-resistant strains with dual carbapenemases causing sepsis are alarming as they are practically untreatable.